PENGARUH KEBIJAKAN MARKETING MIX TERHADAP PEMASARAN BENIH KEDELAI (PT. SANG HYANG SERI CABANG JAWA TIMUR DAN BALI DI MALANG) - Eri Yusnita Arvianti (Universitas Tribhuwana Tunggadewi, 2006)
This study was aimed to elucidate (a) marketing management of soybean seed conducted by PT Sang Hyang seri (Persero) of Malang, (b) problems encountered by PT Sang Hyang Seri in conducting marketing management of soybean seed, and (c) effect of implementation of price and distribution policies on marketing of soybean seed. The Company uses marketing mix soybean which is a combination of product, price, distribution and promotion to market soybean seed. Constraints of production aspect were due to imprecise production planning and marketing period of soybean seed. Distribution aspect faced constraints in the forms of capacities transport minimum and less paying attention of risk storey level. At price aspect produce to be burdened at price height sell resulted from by the level of production cost and also fewer funds to represent constraint at promotion aspect. Result of regression analysis indicated that price variable and distribution influenced storey level marketing of soybean seed